Prosthetic foot design: the significance of the normalized ground reaction force - Bani Hashim, A.Y.; Abu Osman, Noor Azuan; Wan Abas, Wan Abu Bakar; Abdul Latif, L. (2011)
This study maps bones and joints, relate them to the vertical ground reaction forces on gait. Their localities are charted in the form of graph. This is then being exploited as arguments to reason the design of prosthetic foot. The mathematical model is developed and is based on the relationship among the anatomy of bones and joints, the vertical ground reaction forces on certain points as well as the sequence when these points experience the vertical ground reaction forces. Using the model, a custom design prosthetic foot is built using a male subject of size 5 scanned foot image. It is concluded that proper mappings and modeling of foot structure can be used as reference in design and development of prosthetic feet.